Business Network Literature Review: A Mini-Review Approach - Ahmad Munawar, N.; Hadiaty, Fifit; Parantoro, Apri (Dinasti Publisher, 2021)
This study aims to find the formulation of factors that can influence the development of business networks both locally and globally. This study used a qualitative method by reviewing 27 journals from previous researchers. The results of this study indicate that multi-actor factors are useful for understanding business networks. Ex-ante signaling and filtering factors at the contractual relationship formation stage are complementary mechanisms that enhance network performance. Agency approach, structure approach and practice approach affect the performance of the business network. Another factor that can improve the performance of a business network is clustering social audiences in a business information network. Organizational variables such as participatory architecture, organizational integration, and mechanisms play a relevant role in protecting and developing business networks. The next finding is that the management relationship factor can improve the performance of the small and medium business network. Value creation innovation includes new capabilities, technology and processes as well as partnerships for the purpose of co-creation that can reduce risk in the business network. Linkage factors and their effect on network connectivity can play a relevant role in strategic business decisions. The role of dynamic capabilities in encouraging business model innovation, especially in market-oriented small and medium enterprises, can encourage innovation in the business model of the small and medium enterprises themselves. Other factors that can affect the efficiency of a business network are intellectual agility, leadership and micro-enterprise innovation mediated through entrepreneurial leadership. The large structure in a business network can positively affect business performance through linkage mechanisms. Whereas the presence of a large number of affiliates in the first company layer of the affiliate structure causes a decrease in the effect of size on the group level performance of the business. Limited diversification at the business group level in the first corporate layer of the affiliate structure results in reduced returns in terms of risk sharing, because shareholders can reduce their investment, thus negatively impacting the overall group level performance. The role of religion and spirituality in the context of a business network greatly influences the strength of a business network.